1989
DOI: 10.1007/bf00874625
|View full text |Cite
|
Sign up to set email alerts
|

Large earthquakes in the macquarie ridge complex: Transitional tectonics and subduction initiation

Abstract: While most aspects of subduction have been extensively studied, the process of subduction initiation lacks an observational foundation. The Macquarie Ridge complex (MRC) forms the Pacific-Australia plate boundary between New Zealand to the north and the Pacific-Australia-Antarctica triple junction to the south. The MRC consists of alternating troughs and rises and is characterized by a transitional tectonic environment in which subduction initiation presently occurs. There is a high seismicity level with 15 la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Regional magnetic isochron map showing interpreted isochrons (numbered) from Weissel et al [1977], Wood et al [1996], and the PLATES database [ Lawver et al , 2001]. Amount of underthrusting of SEIR crust (labeled) at the Hjort Trench proposed in this paper (large gray dot pattern) is significantly less than that predicted by Weissel et al [1977] and Ruff et al [1989] asterisk pattern) based on the observed truncation of magnetic anomalies 5 through 8 (∼10 to 25 Ma) [ Cande and Kent , 1995] as compared to their conjugate anomalies on the south side of the easternmost segment of the SEIR. Continental crust of the Campbell Plateau (grey‐colored region outlined with a dashed black line) is shallower than 2000 m water depth; oceanic crust created at the extinct MRC spreading center (light gray area) formed from 40 to ∼10 Ma.…”
Section: Geodynamic Setting and Previous Researchmentioning
confidence: 78%
“…Regional magnetic isochron map showing interpreted isochrons (numbered) from Weissel et al [1977], Wood et al [1996], and the PLATES database [ Lawver et al , 2001]. Amount of underthrusting of SEIR crust (labeled) at the Hjort Trench proposed in this paper (large gray dot pattern) is significantly less than that predicted by Weissel et al [1977] and Ruff et al [1989] asterisk pattern) based on the observed truncation of magnetic anomalies 5 through 8 (∼10 to 25 Ma) [ Cande and Kent , 1995] as compared to their conjugate anomalies on the south side of the easternmost segment of the SEIR. Continental crust of the Campbell Plateau (grey‐colored region outlined with a dashed black line) is shallower than 2000 m water depth; oceanic crust created at the extinct MRC spreading center (light gray area) formed from 40 to ∼10 Ma.…”
Section: Geodynamic Setting and Previous Researchmentioning
confidence: 78%
“…Oblique convergence is indicated by the occurrence of thrust-related seismicity along a zone that primarily fi•nctions as a transform boundary [Ruff et al, 1989]. Oblique convergence is indicated by the occurrence of thrust-related seismicity along a zone that primarily fi•nctions as a transform boundary [Ruff et al, 1989].…”
Section: A Sinfilar Evolution Has Been Inferred For the Macquarie Ridgementioning
confidence: 99%
“…Paper number 90GL00714; 0094-8276/90/90GL-00714$03.00 997 Ruff et al [1989]. They found that the mechanism of large events had bimodal distribution; either strike-slip along the ridge axis or dip-slip with the Australia plate subducting beneath the Pacific plate.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the mechanism of large events had bimodal distribution; either strike-slip along the ridge axis or dip-slip with the Australia plate subducting beneath the Pacific plate. Ruff et al[1989] interpreted this complexity as an initiation of the subduction process in this region.…”
Section: Introductionmentioning
confidence: 99%